2008
DOI: 10.1128/jcm.01341-08
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Genotyping and Quantitation of Cytomegalovirus gB Genotypes in Solid-Organ-Transplant Recipients by Use of a Real-Time PCR Assay

Abstract: We have developed a real-time genotyping and quantitative PCR (RT-GQ-PCR) assay to genotype cytomegalovirus (CMV) and quantify viral loads simultaneously in solid organ transplant (SOT) recipients. Special minor-groove DNA-binding probes were designed based on sequence polymorphism in the gB gene to increase genotyping specificity for gB1 to gB4. For validation, 28 samples with known genotypes determined by restriction fragment analysis (RFA) and 121 with unknown genotypes were tested. All samples were from SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 41 publications
2
46
0
Order By: Relevance
“…Further analysis, such as deep sequencing (29) or subcloning of the PCR product amplified from PBMCs obtained from ES patients, is required to confirm mixed populations of the virus in these isolates. Previous studies determined that mixed infections of CMV occurred in 15 to 50% of transplant recipients based on molecular epidemiological analysis of glycoprotein genes (30)(31)(32)(33)(34)(35). Moreover, mixed viral infections have been linked to high viral loads (31,32), delayed viral clearance (31), and higher rates of viral recurrence (31).…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis, such as deep sequencing (29) or subcloning of the PCR product amplified from PBMCs obtained from ES patients, is required to confirm mixed populations of the virus in these isolates. Previous studies determined that mixed infections of CMV occurred in 15 to 50% of transplant recipients based on molecular epidemiological analysis of glycoprotein genes (30)(31)(32)(33)(34)(35). Moreover, mixed viral infections have been linked to high viral loads (31,32), delayed viral clearance (31), and higher rates of viral recurrence (31).…”
Section: Discussionmentioning
confidence: 99%
“…Mixed populations of CMV genomes within an infected individual have been observed by analyzing gB genotypes (122)(123)(124)(125)(126)(127)(128)(129)(130) as well as the genotypes for additional virion envelope proteins: gN, gO, gH, and gL (127)(128)(129). These differences permitted the categorization of 4 polymorphic gB genotypes (131), 7 polymorphic gO genotypes, and 4 polymorphic gN genotypes (132,133).…”
Section: Strain Polymorphism Contributes To Immune Evasionmentioning
confidence: 99%
“…Even cloning of PCR products and subsequent Sanger sequencing do not allow a sensitive assessment of the genotypes present unless an extremely large number of individual clones is sequenced. Improved genotype-specific real-time-PCR-based assays have been established recently for gB and gH genotyping, and these allow simultaneous detection and quantitation of distinct genotypes in mixed infections down to a level of 5% or even less (14,28).In the present study, we determined the relative amounts of different HCMV genotypes in clinical samples from lung transplant patients by using the highly sensitive ultradeep-pyrosequencing (UDPS) technology. UDPS genotyping of three of the most variable genes within the HCMV genome, the gN, gO, and UL139 genes, revealed that there is a substantially higher diversity of HCMV genotype populations in patients with mixed HCMV infection than has been recognized previously and that the HCMV strains show a distinct pattern in…”
mentioning
confidence: 99%
“…Even cloning of PCR products and subsequent Sanger sequencing do not allow a sensitive assessment of the genotypes present unless an extremely large number of individual clones is sequenced. Improved genotype-specific real-time-PCR-based assays have been established recently for gB and gH genotyping, and these allow simultaneous detection and quantitation of distinct genotypes in mixed infections down to a level of 5% or even less (14,28).…”
mentioning
confidence: 99%